Featured Cover. Issue 12 (19th November 2021) - Salinas, Gerardo; Arnaboldi, Serena; Bonetti, Giorgia; Cirilli, Roberto; Benincori, Tiziana; Kuhn, Alexander
Abstract : The cover image is based on the Special Issue Article Hybrid light‐emitting devices for the straightforward readout of chiral information by Gerardo Salinas et al., https://doi.org/10.1002/chir.23370 .